Evaluation of supplemental vitamin E on 56-day feedlot growth performance and plasma tocopherol concentrations in calf-fed Holstein steers. Issue 1 (1st January 2017) - Cano, A. B.; Montano, M.; Salinas-Chavira, J.; Zinn, R. A.
ABSTRACT: Fifty-four Holstein steer calves, divided in two weight groupings (141.2 ± 4.9 kg and 454.2 ± 7.0 kg respectively), were used in a 56-day study to evaluate the influence of supplemental vitamin E on growth performance and plasma vitamin concentrations. Steers were assigned within body weight groupings to 18 pens, 3 steers/pen. Dietary treatments consisted of a steam-flaked corn-based growing-finishing diet supplemented to provide 0, 250, or 500 IU/d of vitamin E as all racemic α -tocopherol. No morbidity was apparent during the course of the study. Calves in the heavier weight grouping had greater average daily gain (24.4%, P  < .01), dry matter intake (54.3%, P  < .01), and lower gain efficiency (40.7%, P  < .01). Vitamin E supplementation did not affect ( P  > .10) feedlot growth performance. Initial and 56-day plasma tocopherol were not influenced ( P  > .10) by weight grouping. Final 56-day plasma tocopherol increased linearly ( P  < .01) with level of vitamin E supplementation. Plasma tocopherol of non-supplemented steers decreased ( P  = .01) from an average initial concentration of 1.66–1.16 ug/mL at day 56. It is concluded that vitamin E supplementation of calf-fed Holstein steers receiving a conventional steam-flaked corn-based growing-finishing diet is not expected to enhance growth performance.